2008
DOI: 10.1111/j.1574-6941.2008.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the pIPO2/pSB102 family of environmental plasmids: sequence, evolution, and ecology of pTer331 isolated from Collimonas fungivorans Ter331

Abstract: Plasmid pTer331 from the bacterium Collimonas fungivorans Ter331 is a new member of the pIPO2/pSB102 family of environmental plasmids. The 40 457-bp sequence of pTer331 codes for 44 putative ORFs, most of which represent genes involved in replication, partitioning and transfer of the plasmid. We confirmed that pTer331 is stably maintained in its native host. Deletion analysis identified a mini-replicon capable of replicating autonomously in Escherichia coli and Pseudomonas putida. Furthermore, plasmid pTer331 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 84 publications
0
48
0
Order By: Relevance
“…Many of the genes located on plasmid pTer331 (Mela et al, 2008) showed increased expression in response to the fungus. The same was true for genes in clusters N (Cf_1047-1074) and O (Cf_2102-2115), both of which carry genes belonging to putative prophages.…”
Section: Horizontal Gene Poolmentioning
confidence: 99%
“…Many of the genes located on plasmid pTer331 (Mela et al, 2008) showed increased expression in response to the fungus. The same was true for genes in clusters N (Cf_1047-1074) and O (Cf_2102-2115), both of which carry genes belonging to putative prophages.…”
Section: Horizontal Gene Poolmentioning
confidence: 99%
“…Both T4A and T4B secretion systems have been shown to translocate or secrete a range of different substrates from DNA bound to protein to single proteins to multisubunit toxins (4, 8, 11, 12, 16, 36, 37, 39-41, 43, 53, 55, 61, 64). The closest homologues of the virB locus are T4A systems encoded by the conjugative plasmids pSB102, pIPO2T, and pTer331 (38,51,60).The best-studied T4SS is the VirB system of Agrobacterium tumefaciens, which is therefore used as a model for the T4A systems. The current model for assembly of the VirB T4SS postulates a core structure in the periplasmic space composed of the proteins VirB6, VirB7, VirB8, VirB9, and VirB10 (13).…”
mentioning
confidence: 99%
“…Both T4A and T4B secretion systems have been shown to translocate or secrete a range of different substrates from DNA bound to protein to single proteins to multisubunit toxins (4, 8, 11, 12, 16, 36, 37, 39-41, 43, 53, 55, 61, 64). The closest homologues of the virB locus are T4A systems encoded by the conjugative plasmids pSB102, pIPO2T, and pTer331 (38,51,60).…”
mentioning
confidence: 99%
“…Of the three mechanisms of lateral gene transfer, conjugation is one of the most important for exchanging genes [275,276]. Plasmids are autoreplicatives extrachromosomal molecules of DNA, mostly circular but otherwise linear [277], and are transmitted both vertically (from mother cell to daughter during bacterial division) and horizontally (from a donor cell to a recipient cell). Plasmids are mosaic genomes that include two distinct regions [278]: (1) skeleton genes, often conserved among members of the same family of plasmids, ensure replication and maintenance of the plasmid in the cell and transfer [279]; and (2) accessory genes encoding functions that are frequently beneficial to the host cell.…”
Section: Lateral Gene Transfer In Rhizosphere and Hydrocarbon Degradamentioning
confidence: 99%